Biopatente und der Mythos des 'Patents auf Leben'. (The Myth of a 'Patent on Life' and Bio-patenting. With English summary.) - Friesenbichler, Klaus S. (2012)
Patents on biotechnological inventions are suspected to create "patents on life". We shed light on arguments which have often been used in the media campaigns of NGOs. While we acknowledge the role of these organisations as seldom critical voices, we conclude that their arguments, at best, only partly reflect the regulatory frame. Undermining biotechnological patents in the absence of objective reasoning weakens the core of an innovative and research driven industry.